Melatonin supplementation to rats subjected to acute swimming exercise: Its effect on plasma lactate levels and relation with zinc - Kaya, O; Gokdemir, K; Kilic, M; Baltaci, AK (Maghira & Maas Publications, 2006)
OBJECTIVE: The objective of the present study is to examine the effect on melatonin supplementation on plasma lactate levels and its relation with zinc in rats subjected to acute swimming exercise. METHODS:Thirty adult male rats of Spraque-Dawley species were allocated to 3 groups, each containing an equal number of rats: general control group which was not subjected to any procedure (Group 1), the group which was subjected to 30 minutes acute swimming exercise (Group 2), and the group which was subjected to 30 minutes acute swimming exercise after 4-week intraperitoneal (i.p.) melatonin (3 mg/kg/day) supplementation. Lactate and zinc levels in the plasma were studied in the blood samples taken from the experimental animals by decapitation method. RESULTS:The animals in the control group, which was not subjected to any procedure (group 1), had higher lactate levels than those in groups 2 and 3 (p < 0,05). Lactate levels in the swimming group supplemented with melatonin (group 3) were lower than those in group 2 (swimming group) (p < 0,05). The highest plasma zinc levels were obtained in the melatonin-supplemented swimming group (group 3) (p < 0,05). Group 2 (swimming control) had the lowest plasma zinc levels (p < 0,05). CONCLUSION:Results of the study demonstrate that melatonin supplementation to rats subjected to acute swimming exercise reduces lactate levels, thereby delaying exhaustion. Increased zinc levels may be mediating this melatonin effect.
Keywords: melatonin; acute swimming exercise; lactate; zinc